PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI PEMISAHAN CAMPURAN UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI - Elisa, Claudia Eva; Muharini, Rini; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe aims of this research were to examine the effect of PjBL on student communicating skill. To achieve the aim, twenty nine students were tested before and after learning through PjBL to measure their communicating skill. The form of this research was Pre-Experimental design with the research plan of single pre-test and post-test researching. The taking sample technique used in this research was purpose sampling. According to wilcoxon test, probability score was less then 0,05 (p>0,05) which meant there was a significant difference of communicating skills at between student before and after learning to PjBL. According to glass test, effect size score was 0,6 which meant PjBL have largest effect on oral communicating skill. According to glass test, effect size score was 1,1 which meant PjBL have largest effect on oral communicating skill. Based on the calculating of the effect size , the applying of PjBL model was highly effect the student’s communicating skills of VII grade students at SMP Negeri 12 Pontianak. Keywords: Project Based Learning, Communicating Ability, Separation Methods